2018
DOI: 10.1016/j.yexmp.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

CD10 inhibits cell motility but expression is associated with advanced stage disease in colorectal cancer

Abstract: Our results suggest that the function of CD10 may change during tumour evolution. It may inhibit cell motility in early-stage disease whilst promoting cell viability in late-stage disease. It has a complex role and further studies are needed to elucidate the suitability of CD10 as a prognostic marker or therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…CD10 is normally expressed in brush border of the small intestine [37]. It is reported that CD10 positive CRCs tend to have more venous invasion and/or liver metastasis [8,27,29,37]. In our study too, CD10 positive CRCs had propensity to develop venous invasions (p < 0.001) and/or liver metastases though it was statistically not significant (p = 0.060).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…CD10 is normally expressed in brush border of the small intestine [37]. It is reported that CD10 positive CRCs tend to have more venous invasion and/or liver metastasis [8,27,29,37]. In our study too, CD10 positive CRCs had propensity to develop venous invasions (p < 0.001) and/or liver metastases though it was statistically not significant (p = 0.060).…”
Section: Discussionmentioning
confidence: 42%
“…Unclassified type CRCs were most common in our study as well, however in comparison to their report, we had more cases with small-intestinal type CRCs than large-intestinal type. Although large-intestinal type CRCs were known for less likelihood to develop vascular and/or lymphatic invasions, their And it was reported that CD10 positive CRCs had more liver metastases [8,27,29]. This study was able to add the characteristic that small-intestinal type was significant risk factor for liver metastasis in CRC and independent of other variable factors.…”
Section: Discussionmentioning
confidence: 74%
“…16 Epithelial immunoexpression of CD10 was found to be associated with tumor grade, stage, and lymph node invasion in colorectal cancer. 17 On the other hand, the stromal immunoexpression of CD10 was found to be associated with a larger tumor size in colorectal carcinoma, 18 lymph node metastasis, recurrence and disease-free in breast carcinoma, [19][20][21] and gastric carcinoma. 22 Limitations of the study: This study utilized tissue microarray material, which includes representative cores of tissue.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies, mainly conducted in Japan, have reported CD10 expression in CRC with conflicting results. Some data suggest an increase in tumoural CD10 expression in advanced CRC tumour stages, based on Duke's classification [14,19], lymphatic invasion [20], lymph node metastasis [9,14,20], and liver metastasis [8,[15][16][17][18], while others found no association with histopathological features such as tumour size or invasion depth [9,15,[20][21][22], TNM staging [9], or lymph node or distant metastasis [9,15,21,22,28]. The majority of these studies are Asian single-centre cohorts, ranging in size from 30 to a few hundred patients.…”
Section: Discussionmentioning
confidence: 99%
“…The role of CD10 in colorectal cancer is controversially discussed in the literature, which is currently primarily based on studies conducted in Japan [8,9,[14][15][16][17][18][19][20][21][22]. Furthermore, the impact of CD10 expression on patient prognosis and survival remains unresolved, due to conflicting published data [9,17,22,23].…”
Section: Introductionmentioning
confidence: 99%